PERAN KOMUNIKASI PEMASARAN DALAM MENINGKATKAN BRAND AWARENESS DAN PENJUALAN: PENDEKATAN STRATEGI - Yohanes Felik; Blasius Manggu; kusnanto (Mount Hope Management International Journal, 2024)
Marketing communications is a key element in a marketing strategy that aims to inform, persuade and remind consumers about a company's products or services. This article explores the role of marketing communications in increasing brand awareness and sales. Through a comprehensive literature review and case study analysis, this article highlights the importance of combining marketing communication tools such as advertising, sales promotion, public relations, and digital marketing. The research results show that effective integration of these tools can create a significant impact on business success.